2009
DOI: 10.2147/jpr.s7903
|View full text |Cite
|
Sign up to set email alerts
|

Patient perception of pain care in hospitals in the United States

Abstract: Study objectiveAssessment of patients’ perception of pain control in hospitals in the United States.BackgroundLimited data are available regarding the quality of pain care in the hospitalized patient. This is particularly valid for data that allow for comparison of pain outcomes from one hospital to another. Such data are critical for numerous reasons, including allowing patients and policy-makers to make data-driven decisions, and to guide hospitals in their efforts to improve pain care. The Hospital Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
0
48
0
1
Order By: Relevance
“…Ineffective pain management infl uences patient recovery. Ineffective pain management may also impact the organization as a consequence of increased readmissions, prolonged length of stay, and poor clinical outcomes ( Dunwoody et al, 2008 ;Gillaspie, 2010 ;Gupta, Daigle, Mojica, & Hurley, 2009 ). Innis, Bikaunieks, Petryshen, Zellermeyer, and Ciccarelli (2004) maintain that the "most common barrier to successful pain management is the failure to assess.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Ineffective pain management infl uences patient recovery. Ineffective pain management may also impact the organization as a consequence of increased readmissions, prolonged length of stay, and poor clinical outcomes ( Dunwoody et al, 2008 ;Gillaspie, 2010 ;Gupta, Daigle, Mojica, & Hurley, 2009 ). Innis, Bikaunieks, Petryshen, Zellermeyer, and Ciccarelli (2004) maintain that the "most common barrier to successful pain management is the failure to assess.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Some providers are financially incentivized to aggressively treat pain because their salaries are tied to patient satisfaction scores that encompass pain control metrics. [48][49][50][51][52][53][54][55] Balancing the risks and benefits of opioid prescribing is difficult when the physician faces pressure from the patient and healthcare system. 18,56 We characterized opioid receipt at hospital discharge among opioid naïve medical and surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…The geographic difference by state is common in healthcare. For instance, Gupta et al found a significant difference in patient pain care perception between the states [17], while Nothelle et al reported a difference in potentially inappropriate medication use between US regions [18]. Similarly, Cole, Wilson, and Trivedi reported state variation in quality outcome for community health centers [19].…”
Section: Discussionmentioning
confidence: 99%